From Husserl to Merleau-Ponty: Tracing the Arc of Phenomenology (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
This research traces the key developments in phenomenological thought from its inception with Edmund Husserl to its evolution under Maurice Merleau-Ponty. The primary objective is to understand the continuity and divergence in their perspectives, and the influence on phenomenology’s progression as a philosophical tradition. The study employs a conceptual and thematic analysis method to elucidate these developments by examining their foundational texts. The findings reveal a nuanced understanding of this evolution, highlighting both Husserl’s establishment of transcendental phenomenology focused on pure consciousness and Merleau-Ponty’s transformative turn toward embodied experience. By synthesizing connections between their projects, this analysis provides a comprehensive view of the arc of phenomenological thought.Keywords: Phenomenology, Husserl & Merleau-Ponty, Intentionality, Consciousness, Embodiment
Keywords: Phenomenology; Husserl & Merleau-Ponty; Intentionality; Consciousness; Embodiment; Thematic Analysis